Fabrication of Glass Serpentine Microchannels using Rotary Ultrasonic Milling - Jain, Apoorv (My University, 2017)
Microchannel is the basic structure in any microfluidic device to control, deliver, manipulate and store the liquid. These microchannels are typically made of silicon, metal, or glass and often feature circular, rectangular or trapezoidal cross sections, ranging in terms of the hydraulic diameter from 1 μm to 1000 μm. Various lithographic micromachining techniques are widely used to fabricate the microchannels on such type of substrates. Additive manufacturing is one of the silicon micromachining techniques of producing parts by successive deposition of layers of material as in the case with rapid prototyping. A new technique for creating serpentine microchannels has been produced on soda lime glass with the help of Rotary Ultrasonic Milling (RUM). Microchannels are the basic structure for any microfluidic device to handle, deliver, operate and to collect the liquid. There are various technologies by which these microchannels are being fabricated but they are more time consuming. With RUM any type of complex profile can be easily made in lesser time and that too with good precision. In this paper serpentine microchannels have been fabricated characterized by scanning electron microscope and profile projector. The various output parameters were observed from the fabrication of the serpentine microchannels like tool wear, surface roughness and edge chipping. The best results which were obtained by the input variables were spindle speed 4500 rpm, feed rate 3 mm/min and amplitude 20 μm.
Keywords: Microchannels; Glass; Micromachining; Rotary Ultrasonic Milling.